Media Pembelajaran Berbasis Android Pada Materi Fotografi Dasar - Nasruha, Muhammad Khalish; Akhyar, Ramaulvi Muhammad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research created an Android-based learning media product using the iSpring Suite to evaluate its feasibility before implementing it in the program's basic subjects for students in class X-DKV. The production of this learning media product categorizes research as a development study or R&D, using the 4D development paradigm. Data is collected through observation, interviews, and questionnaires, then analyzed using quantitative descriptive analysis. This study involved 2 media experts, 1 material expert, and 14 students of class X-DKV as product test subjects. Based on the results of the feasibility validation and trial of android-based learning media products by media experts, material experts and students, the results were very feasible. The average value of material feasibility validation is 54 more than 50.4 including the